Critical Discourse Analysis of the Internationalization of Bahasa Indonesia in Online News: Norman Fairlough’s Description Approach: Analisis Wacana Kritis Internasionalisasi Bahasa Indonesia dalam Berita Daring: Pendekatan Deskripsi Norman Fairlough - Adiwinata, Akbar (Journal of Literature and Education, 2025)
The purpose of this study is to examine online news media reports about the internationalization of Bahasa Indonesia in Kompas.id. The focus of this research is to identify the representations of Bahasa Indonesia and to understand the reality that is constructed in the news. This research used a qualitative method in analyzing four online news texts by applying Norman Fairlough’s ideas of textual dimensions (description) regarding the Critical Discourse Analysis (CDA). Data collection techniques were conducted through documentation, while data validity was obtained through internal validity. Based on the results of the research, it can be concluded that the news of the internationalization of Bahasa Indonesia in online news media Kompas.id forms a discourse that emphasizes nationalism and pride in UNESCO recognition. Specific lexical choices such as golden door, national pride, and historic milestone reinforce a narrative of achievement. However, Kompas.id minimizes critical perspectives on ongoing challenges such as the need for academic vocabulary development and international curriculum alignment. As the result, online news media Kompas.id shows how the media shapes public understanding of the position of Bahasa Indonesia at the global level.